Moderation of Intellectual Intelligence on the Effect of Individual Behavior, Modern Living Environment, and Financial Well-Being on Women's Financial Literacy Capacity - Sihar Tambun; Fitri Nurwanti (Program MM Universitas Surabaya, 2023)
Purpose: This study aims to prove that the moderation of intellectual intelligence positively affects individual behavior, the modern living environment, and the financial well-being of women's financial literacy capacity. Method: The sample in this study consisted of 328 respondents in Indonesia. Data quality testing in this study used Partial Least Square (PLS) analysis, a Structural Equation Modeling (SEM) equation model with a variance-based or component-based structural equation modeling approach. Result: The study results show that intellectual intelligence cannot moderate the effect of individual behavior on women's financial literacy capacity, but intellectual intelligence can moderate the effect of the modern living environment and financial well-being on women's financial literacy capacity. High intellectual intelligence and utilizing the high intellectual intelligence will increase individual behavior, affecting women's financial literacy capacity. The results of this study recommend that women having good individual behavior and financial well-being in the modern era reinforced by high intellectual intelligence can encourage individuals in Indonesia to increase women's financial literacy capacity.